AUDIT DELAY MEMEDIASI PENGARUH AUDIT FEE, AUDIT TENURE DAN AUDIT CAPACITY STRESS TERHADAP KUALITAS AUDIT PADA PERUSAHAAN INFRASTRUKTUR, UTILITAS DAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2022 - OKTA VIARNI, WINDY; SURYADI, NANDA; YUSNELLY, ARIE; RAHMA, SITTI (JURNAL AKUNTANSI DAN KEUANGAN, 2023)
This research aims to determine the effect of audit fees, audit tenure and audit capacity stress mediated by audit delay on audit quality in Infrastructure, Utilities and Transportation Companies listed on the Indonesia Stock Exchange in 2019-2022. This research is quantitative research. The population in this study was 113 Infrastructure, Utility and Transportation Companies in 2019-2022. The number of samples in this research was 21 samples of Infrastructure, Utilities and Transportation companies listed on the Indonesia Stock Exchange in 2019-2022. The data analysis method used is path analysis using SEM-SmartPLS 3.0 software as a test tool for data processing. The research results show that audit fees and audit capacity stress do not have a significant effect on audit quality, audit tenure and audit delay have a significant effect on audit quality. Audit tenure and audit capacity stress have an effect on audit delay, audit fees have no effect on audit delay, audit fees have no effect on audit quality through audit delay as a mediating variable, audit tenure and audit capacity stress have an effect on audit quality through audit delay as a mediation